Chronic hyperinsulinemia promotes human hepatocyte senescence - Ritesh K. Baboota; Rosa Spinelli; Malin C. Erlandsson; Bruna B. Brandao; Marsel Lino; Hong Yang; Adil Mardinoglu; Maria I. Bokarewa; Jeremie Boucher; C. Ronald Kahn; Ulf Smith (Elsevier, 2022)
Objective: Cellular senescence, an irreversible proliferative cell arrest, is caused by excessive intracellular or extracellular stress/damage. Increased senescent cells have been identified in multiple tissues in different metabolic and other aging-related diseases. Recently, several human and mouse studies emphasized the involvement of senescence in development and progression of NAFLD. Hyperinsulinemia, seen in obesity, metabolic syndrome, and other conditions of insulin resistance, has been linked to senescence in adipocytes and neurons. Here, we investigate the possible direct role of chronic hyperinsulinemia in the development of senescence in human hepatocytes. Methods: Using fluorescence microscopy, immunoblotting, and gene expression, we tested senescence markers in human hepatocytes subjected to chronic hyperinsulinemia in vitro and validated the data in vivo by using liver-specific insulin receptor knockout (LIRKO) mice. The consequences of hyperinsulinemia were also studied in senescent hepatocytes following doxorubicin as a model of stress-induced senescence. Furthermore, the effects of senolytic agents in insulin- and doxorubicin-treated cells were analyzed. Results: Results showed that exposing the hepatocytes to prolonged hyperinsulinemia promotes the onset of senescence by increasing the expression of p53 and p21. It also further enhanced the senescent phenotype in already senescent hepatocytes. Addition of insulin signaling pathway inhibitors prevented the increase in cell senescence, supporting the direct contribution of insulin. Furthermore, LIRKO mice, in which insulin signaling in the liver is abolished due to deletion of the insulin receptor gene, showed no differences in senescence compared to their wild-type counterparts despite having marked hyperinsulinemia indicating these are receptor-mediated effects. In contrast, the persistent hyperinsulinemia in LIRKO mice enhanced senescence in white adipose tissue. In vitro, senolytic agents dasatinib and quercetin reduced the prosenescent effects of hyperinsulinemia in hepatocytes. Conclusion: Our findings demonstrate a direct link between chronic hyperinsulinemia and hepatocyte senescence. This effect can be blocked by reducing the levels of insulin receptors or administration of senolytic drugs, such as dasatinib and quercetin.